1998
DOI: 10.1101/gad.12.20.3149
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptors—new ligands and new possibilities: Figure 1.

Abstract: Nuclear hormone receptors comprise a large superfamily of ligand-modulated transcription factors that, in part, mediate response to steroids, retinoids and thyroid hormones and play key roles in development and body physiology (for review, see Beato et al. 1995;Enmark and Gustaffson 1996;Willy and Mangelsdorf 1998). Ten years ago the first orphan nuclear receptors were isolated, raising the first portents toward a new era in physiology (Giguere et al. 1988). Although structurally related to the known receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(175 citation statements)
references
References 48 publications
1
169
0
5
Order By: Relevance
“…Since some of the CYPs that are regulated by PXR and CAR are involved in steroid metabolism, it is not surprising that the activities of both xenosenors are also modulated by steroids [38]: PXR is activated by pregnanes, progesterone and glucocorticoids [4,5] whereas androstane metabolites, estrogens and progesterone affect CAR activity both positively and negatively [10,[39][40][41].…”
Section: Xenosensors In Steroid Biosynthesis and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Since some of the CYPs that are regulated by PXR and CAR are involved in steroid metabolism, it is not surprising that the activities of both xenosenors are also modulated by steroids [38]: PXR is activated by pregnanes, progesterone and glucocorticoids [4,5] whereas androstane metabolites, estrogens and progesterone affect CAR activity both positively and negatively [10,[39][40][41].…”
Section: Xenosensors In Steroid Biosynthesis and Metabolismmentioning
confidence: 99%
“…In patients, long-term -7 -treatment with rifampicin, a strong human PXR activator, phenobarbital or other anti-convulsants interferes with the bioavailability and therapeutic efficacy of coadministrated corticosteroids and steroid-based oral contraceptives [38,43]. The effect of drugs and xenobiotics on endogenous steroid levels is less clear because of highly efficient compensatory mechanisms that control steroidogenesis and metabolism.…”
Section: Xenosensors In Steroid Biosynthesis and Metabolismmentioning
confidence: 99%
“…The superfamily includes receptors for androgen, glucocorticoid, progesterone, vitamin D3, thyroid hormone and retinoic acid, as well as receptors activated by peroxisome proliferators, bile acid-, prostaglandin-and benzoate-activated receptors (Blumberg and Evans, 1998;Makishima et al, 1999;Mangelsdorf et al, 1995;Parks et al, 1999;Wang et al, 1999). ERa is required for regulating the development and in the maintenance of the female and male reproductive systems, in bone maintenance and in the cardiovascular system, as well as being signi®cant for certain brain functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…23 Over the past 10 years as ligands for many of these receptors have been discovered, including the oxysterols for the LXRs, the remaining members of this 'orphan' class have come to be recognized as a special group the regulation of which is largely driven by their rapid and transient expression in response to intracellular signals. 24 For example, Ruis et al 15 identified a set of three cAMP response elements in the NOR-1 promoter that increases gene transcription in response to cAMP levels.…”
Section: Discussionmentioning
confidence: 99%